Стратегічні й інституційні аспекти реалізації політики маркетингу територій в органах місцевого самоврядування - Таранич, А.В.; Хаджинов, І.В. (Економічний вісник Донбасу, 2026)
В роботі розкрито наукові та правничі засади розвитку маркетингу територій, висвітлено внесок провідних наукових шкіл (класичної маркетингової, регіонально-економічної, урбаністичної, соціокультурної та публічно-управлінської). Значну увагу приділено ролі брендингу територій як інструменту стратегічного управління, а також характеристиці механізмів та інструментів, які застосовують органи місцевого самоврядування для формування ідентичності, підвищення конкурентоспроможності та налагодження ефективних комунікацій. Проведено аналіз стратегічних і інституційних аспектів реалізації політики маркетингу територій у діяльності органів місцевого самоврядування, виявлено умови, що забезпечують формування конкурентоспроможного та впізнаваного бренду громади, а також визначено фактори, які підвищують ефективність маркетингової політики та її роль у соціально-економічному розвитку територій. The study reveals the scientific and legal foundations of territorial marketing and highlights the contribution of leading scholarly traditions – including the classical marketing school, regional-economic approaches, urban studies, sociocultural perspectives, and public administration research. Considerable attention is devoted to the role of place branding as a strategic management instrument, as well as to the mechanisms and tools employed by local self-government bodies to shape territorial identity, enhance competitiveness, and establish effective communication practices. An analysis of the strategic and institutional aspects of territorial marketing policy implementation within local self-government has been conducted, identifying the conditions that ensure the formation of a competitive and recognizable community brand, as well as the factors that contribute to the effectiveness of marketing policy and its role in the socio-economic development of territories. The study determines the specific features of the integrated influence exerted by territorial marketing policy on the social, cultural, and communicative environment of local communities. This approach enabled the formation of a contemporary understanding of territorial marketing as a strategic management tool that integrates place branding, public communication, spatial development policy, and investment attraction. An important factor is the legitimization of place branding and territorial marketing as components of state policy and regional development strategies, which creates opportunities for systemic, coherent, and long-term implementation of marketing policy by communities, particularly in the context of post-war recovery. The components of territorial marketing policy are characterized in detail, and their generalization has made it possible to determine their high effectiveness in creating a competitive, recognizable, and resilient community brand. Place branding, public communication, infrastructure development, cultural and educational events, investment marketing, and digital tools constitute a synergistic system aimed at strengthening territorial reputation, attracting resources, and improving residents’ quality of life. The comprehensiveness and complementarity of these tools ensure the capacity of communities to adapt to external challenges, strengthen their competitive advantages, and develop productive communication with relevant stakeholders. The study identifies the prerequisites for implementing territorial marketing policy that ensure its economic sustainability, support social cohesion, form a positive territorial image, and reinforce the community’s position in a competitive environment. Territorial marketing policy is increasingly acquiring a systemic character within community-level program planning, including the development of strategic plans, marketing and communication strategies, investment proposals, and digital transformation projects. The implementation of such a model contributes to building a strong territorial image, attracting new partners, and ensuring sustainable development under conditions of regional competition. It is concluded that territorial marketing should be regarded as a key managerial instrument of local self-government, capable of ensuring comprehensive recovery, modernization, and sustainable development of territorial communities amidst dynamic change and post-war transformation.